Influência de hábitos maternos na concentração de bifenilos policlorados (PCBs) em soro de cordão umbilical - Mohr, Susana (2010)
The polychlorinated biphenyls (PCBs) are synthetic aromatic chemicals mixtures industrially used since the 30 s decade. Due to its physics characters, as electric current and high temperature tolerance, it has been applied mainly as dielectrics fluids in capacitors and transformers. They toxic effect was evidenced from realized studies, and its extinguish became a challenge. Its prohibition started in United States, in 1976, but only in 1981 in Brazil, although its use in old electrics equipments are still yet consent, until its replacing. The environmental contamination mainly comes out due an inappropriate discard of old electrics equipments, which affect the soil and water. These compounds have a fat great attractive force, becoming accumulated in human and animals adipose tissues. The mainly reason of human contamination is the contaminated foods ingestion, in special, the animal foods source. Due its toxicity and great stability, the objective of this work was to determine the PCBs levels in umbilical cord serum collected from 148 donors that had your children in the Santa Maria University Hospital (HUSM) in 2006, checking the connect with demographic and custom life of donors and the infants information, obtained through questionnaire. The PCBs residues were determinate by gas chromatography with electron-capture detection (GC-μECD), after acid digestion. The confirmation was carried out on a gas chromatography coupled with mass spectrometer (GC/MS). The mean values detected were 0,18 ng mL to PCB 28, 1,71 ng mL to PCB 52, 0,82 ng mL to PCB 153, 2,45 ng mL to PCB 138 and 1,49 ng mL to PCB 180. The most frequent was the PCB 180, detected in 63,5% of samples, followed by PCBs 180 (55,4%), 52 (54,7%), 153 (51,4%) and 28 (19,9%). The PCBs 153 and 180 concentrations were negatively correlation with donors height, while the PCB 52 obtained positive correlation. The PCBs 138 and 180 concentrations were correlation with low development of infants, negatively affecting your length, while the PCB 28 obtained express difference on infants that had weight and head circumference higher. In respect to alimentary habits, express difference was found in PCB 153 concentration in function of fruits consumption: showed a concentration higher in the consumers class of this food. The PCB 153 higher concentration in the class donors that required a forceps delivery significantly disagreed that the others. The donors that lived out of Santa Maria city showed the PCBs 153 and 180 concentrations higher, obtained express difference that the class who lived in Santa Maria city, while the donors that had suffered abortion had higher PCB 52 concentrations, statistically differing for the no abortion class. The birth weights class of infants had higher PCB 52 concentration too, with express difference of normal birth weights class. With regard to malformation presence on infants, significant correlation were found with PCBs 28, 52 e 180 concentrations, that showed higher values in the malformation class. This research results showing that the PCBs presence in the umbilical cord serum, at significant levels, may negatively influence on the infants formation and development, resulting infants with low birth weight, small length and with some kind of malformation presence. As well as the infant, the mother also takes the consequences with PCBs significant levels in the umbilical cord serum, as abortion and difficulty on delivery moment. Literature references were not found about the influence of PCBs on infants malformation, what carry out to deduce that it s the first research about it.